Direct oxidation of benzene to phenol in a microreactor: Process parameters and reaction kinetics study. (31st December 2021) - Zhao, Hailing; Liu, Saier; Shang, Minjing; Su, Yuanhai
Highlights: Synthesis of phenol from benzene and H2 O2 was conducted in microreactors. Effects of various parameters on the oxidation process were investigated. The actual residence time was obtained considering the H2 O2 decomposition. A reaction kinetic model was developed with understanding the reaction network. Abstract: The direct synthesis of phenol from benzene and hydrogen peroxide was conducted in a microreactor. The effects of process parameters such as temperature, catalyst concentration, residence time, and molar ratio of hydrogen peroxide to benzene on the reaction performance were investigated systematically. The phenol yield could reach 15% while the selectivity was 94% with the set residence time of only 60 min at 55 ℃. Furthermore, a novel method was proposed to calculate the actual residence time for the reaction process with the in-situ produced gas due to the hydrogen peroxide decomposition. The actual residence time was found to be much shorter than the set residence time, especially at high temperatures. The reliability of this method at a certain temperature was verified with the kinetic study. The activation energies of phenol synthesis, hydrogen peroxide decomposition and p-benzoquinone formation were determined to be 99.52 KJ/mol, 99.43 KJ/mol and 63 KJ/mol, respectively.